A new proposed tumor-node-metastasis-age staging system for stage IV medullary thyroid carcinoma based on the SEER database - Li, Man (Am J Transl Res, 2021)
Medullary thyroid carcinoma (MTC) is a rare and lethal cancer. There are currently controversies regarding its staging. This study aimed to verify the significance of the patient’s age in the prognosis of MTC and propose its addition to the current staging system. Data on cancer-specific survival (CSS) from the Surveillance, Epidemiology, and End Results database between 2010 and 2015 were used. X-Tile, nomograms, Cox proportional hazards regression analysis, Kaplan-Meier curves, and log-rank tests were used to evaluate mortality rates to create a new staging system. A total of 849 patients were included. Patients were divided into three categories based on their ages at diagnosis: ≤41 years, n = 224 (26.4%); 42-71 years, n = 516 (60.8%); and ≥72 years, n = 109 (12.8%). Independent factors for survival in the multivariate analysis included age (42-71 years, hazard ratio [HR], 2.81, 95% confidence interval [CI], 1.07-7.42; ≥72 years, HR, 8.71, 95% CI, 2.88-26.34), T stage (T2, HR, 3.60, 95% CI, 1.31-9.88), and M stage (M1, HR, 8.43, 95% CI, 4.40-16.16), with P<0.05. The Harrell’s concordance index for tumor node metastasis (TNM) nomogram and TNM-age nomogram was 0.904 and 0.908, respectively. The areas under the curve (AUCs) for a 3-year CSS were 0.88 and 0.873, respectively. The corresponding AUCs for a 5-year CSS were 0.892 and 0.888, respectively. A new TNM-age staging system based on cancer-specific mortality rate analysis is proposed. This system provides a more accurate risk stratification and ensures more rational treatment measures for patients with stage IV MTC.